The preparticipation physical examination: An update - Seto, C. K. (Clinics in Sports Medicine, 2011)
The evolution of the preparticipation physical examination (PPE) in the United States continues to advance. In May 2010, the fourth edition of the Preparticipation Physical Examination Evaluation (PPE-4) monograph was published. The monograph is a product reflecting the collaborative efforts of 6 author societies. This article provides a brief historical review of the PPE and then highlights the recent changes and updates contained in the PPE-4 monograph, including cardiovascular screening in athletes. New recommendations to include the PPE in all well-child care visits and the need to develop a nationwide standard for the PPE are discussed.